Studies on interaction of oligoadenylates with proteins in vitro by MALDI-TOF mass spectrometry - Levchenko, S.M.; Rebriev, A.V.; Tkachuk, V.V.; Dubey, L.V.; Dubey, I.Ya.; Tkachuk, Z.Yu. (Вiopolymers and Cell, 2013)
Aim. To investigate the ability of «core» 2'-5'- and 3'-5'-oligoadenylates (OA) to interact with α-interferon – a key protein of the 2'- 5'-OAS/RNAase L system responsible for antiviral cell defense. Methods. MALDI-TOF mass spectrometry was used in the studies on protein-ligand interactions. Results. It was shown that 2'-5'-A3 and its epoxy-modified analog 2'-5'-A3-epo can bind to α-interferon in vitro. 3'-5'-tri- adenylate is also capable of binding to this protein. One to five ligand molecules can bind simultaneously to the molecule of α-interferon. At the same time, all studied oligonucleotides do not bind to insulin. Conclusions. It was established that «core» 2'-5'- and 3'-5'-triadenylates are capable of multiple interaction with α-interferon to form stable complexes. However, they do not bind to insulin which is not involved in the 2'-5'-OAS/RNAase L system. Мета. Дослідити здатність «корових» 2'-5'- і 3'-5'-олігоаденілатів взаємодіяти з α-інтерфероном – ключовим білком системи 2'-5'-ОАС/РНКаза L, відповідальної за противірусний захист клітини. Методи. Для вивчення взаємодій білок–олігонуклеотид використано метод мас-спектрометрії MALDI-TOF. Результати. Встановлено здатність 2'-5'-А3 та його епокси-модифікованого аналога 2'-5'-А3-epo зв’язуватися з α-інтерфероном in vitro. З цим білком може також взаємодіяти і 3'-5'-триаденілат. При цьому до молекули α-інтерферону одночасно може приєднуватися від однієї до п’яти молекул ліганду. У той же час з інсуліном усі досліджені олігонуклеотиди не зв’язуються. Висновки. Показано, що «корові» 2'-5'- і 3'-5'-триаденілати множинно взаємодіють з α-інтерфероном з утворенням стійких комплексів. Однак вони не зв’язуються з інсуліном, який не є компонентом системи 2'-5'-ОАС/РНКаза L. Цель. Исследовать способность «коровых» 2'-5'- и 3'-5'-олигоаденилатов взаимодействовать с α-интерфероном – ключевым белком системы 2'-5'-ОАС/РНКаза L, ответственной за противовирусную защиту клетки. Методы. Для изучения взаимодействий белок–олигонуклеотид использован метод масс-спектрометрии MALDI-TOF. Результаты. Установлена способность 2'-5'-А3 и его эпокси-модифицированного аналога 2'-5'-А3-еpo связываться с α-интерфероном in vitro. С этим белком может также взаимодействовать и 3'-5'-триаденилат. При этом к молекуле α-интерферона одновременно может присоединяться от одной до пяти молекул лиганда. В то же время с инсулином все изученные олигонуклеотиды не связываются. Выводы. Показано, что «коровые» 2'-5'- и 3'-5'-триаденилаты способны к множественному взаимодействию с α-интерфероном с образованием устойчивых комплексов. Однако они не связываются с инсулином, не являющемся компонентом системы 2'-5'-ОАС/РНКаза L.